TRANSVERSUS ABDOMINIS RELEASE: A CASE REPORT - Aleksandar Mitevski; Ilija Milev; Shenol Tahir; Nikola Trokovski; Petar Markov; Nikoloska, Katerina (Association of Albanian Medical Doctors in Macedonia, 2020)
Introduction: Patients with large abdominal wall defects experience significant deformity, pain and decreased energy due to a loss of normal abdominal wall mechanics, severely impacting their quality of life.Reconstructive techniques for complex ventral hernia repair are numerous but most of them are unable to achieve the goals of hernioplasty. Posterior component separation with transverses abdominis muscle release (TAR) is a novel approach that offers a solution for complex ventral hernias. Case: A 59 year old patient was admitted to our hospital for treatment of clinically and radiologically verified incisional hernia with 20% loss of domain characteristics, acquired after cesarean section and hysterectomy. Discussion/Conclusion: Typical reconstructive techniques may struggle to reestablish abdominal domain and to create a lasting repair. Posterior component separation with transversus abdominis release is a novel technique that offers a durable solution to a variety of complex ventral hernias.The lack of sufficient tissue requires the insertion of prosthetic material or transposition of autologous material to bridge the fascial gap.Retromuscular or sublay hernia repair with mesh has proven to be a durable technique for ventral hernia defects, and completely avoids subcutaneous flap elevation. TAR allows for significant posterior rectus fascia advancement, wide lateral dissection, preservation of the neurovascular supply, avoids subcutaneous tissue undermining and provides a large space for mesh sublay which allowsfor bilaminarin growth of the mesh.
Keywords: Complex hernia; incisional hernia; abdominal hernia repair; transverse abdominal muscle release; TAR